The Effects of Institution-Driven Entrepreneurial Education in Chinese Universities: A Qualitative Comparative Analysis Approach - Liu, Rongzhi; Huo, Yuxin; He, Jing; Zuo, Dun; Qiu, Zhiqiang; Zhao, Jun (Frontiers in Psychology, 2021)
This study aims to explore the effects of entrepreneurship education, by examining the influences of the Curriculum system, teaching team, design of practical program and the institutional systems on universities’ entrepreneurial education performance. It employs a case-based approach—Qualitative Comparative Analysis (QCA). Data was collected from 12 universities which were typical cases in the implementation of entrepreneurial education. The four dimensions of entrepreneurship education are taken as the conditional indicators. The software fsQCA3.0 is used to analyze the necessary conditions and condition combination of the truth table.There are three sets of condition combinations of intermediate solution that results in high level of entrepreneurial education performance: (1)when there is a higher level of credit ratio of entrepreneurship courses and more Practical platform platforms, even the entrepreneurship education system and mechanism is less mature, the level of entrepreneurial education performance is high; (2) With higher credit ratio of entrepreneurship courses , higher quality of teaching team and higher level of Practical platform platform, the level of entrepreneurial education performance is high;(3) with higher level of credit ratio of entrepreneurship courses and more Practical platform platforms, as well as mature entrepreneurship education system and mechanism, even if the quality of teaching team is lower, the level of entrepreneurial education performance is also satisfied. The dimensions of entrepreneurship education can be expanded and there are many other factors affecting entrepreneurial performance, so it is necessary to constantly integrate the other possible factors.This study emphasizes the significance of viewing the entrepreneurial education as a muti dimension concepts by targeting different kinds of player. Furthermore, it employs a case-based approach to identify configurations of the antecedent attributes of the curriculum system, teaching team, design of practical program and the institutional systems, and their influence on universities’ entrepreneurial education performance.